Transcriptomic and histological characteristics of innate immune activation in brain parenchyma in a rat model of neonatal intraventricular hemorrhage - Miriam Zamorano; Sanjna Udtha; Aidan M. Collier; Erica Underwood; Razan El Sayed; Ankit Agarwal; Devin S. Hatchell; Chunfeng Tan; Paul J. Nietert; Scott D. Olson; Brandon A. Miller (Fluids and Barriers of the CNS)
Abstract Background Intraventricular hemorrhage (IVH) remains a major complication in preterm infants with lifelong sequelae. There is no effective treatment for IVH other than supportive care and surgery for post-hemorrhagic hydrocephalus. We previously reported that the innate neuroimmune response in an animal model of IVH was dependent on developmental stage, only occurring in older animals. Methods This study utilized a lysed-blood injection model of IVH in rats. This model specifically captures the effects of blood products released by IVH on brain parenchyma. We performed RNAseq and differential gene expression analysis on CD11b/c-positive cells in the brain (microglia/macrophages) to define gene expression in innate immune cells after IVH. We examined CD68 expression, a marker of activated microglia/infiltrating macrophages, in the periventricular white matter after IVH over 90 days. Using IBA1 staining with skeletonized branch analysis and secondary individual cell Sholl analysis, we characterized morphological changes in innate immune cells after IVH. Glial fibrillary protein (GFAP) staining was used to assess astrogliosis and chronic glial scar formation after IVH. We also examined CD68 expression in brain samples from human infants with or without IVH. Results RNAseq of isolated innate immune cells showed significant differences in cytokine-mediated gene expression at 24 h in IVH versus control animals. CD68 expression in white matter decreased overall with time and was elevated at 7 days in the IVH group compared to controls. IBA1 labeling, when analyzed across all time points, showed significant changes to microglial/macrophage branch number, branch area, and soma area after IVH. Sholl analysis of individual IBA1 labeled cells showed an effect of time but not IVH on microglial/macrophage morphology. At the chronic timepoint of 90 days, IVH induced astrogliosis at the margin of the lateral ventricle. A brain sample from a human infant with IVH showed increased CD68 expression throughout the occipital cortex compared with a non-IVH control, indicating immune activation in brain parenchyma after IVH. Conclusions Intraventricular blood products induce a robust innate immune response shortly after injection. RNAseq and CD68 counts are more sensitive to differences between groups than morphological immune cell analysis. Gliosis at the edge of ependyma occurs over time. These results help establish the timeline of inflammation after IVH to better define the window for treating IVH-associated inflammation and subsequent brain injury.